Views of primary school teachers towards the remedial mathematics resource workshop in Brunei Darussalam - Teng, Leong Koay; Lowrence Mundia; Lina Mak (Universiti Kebangsaan Malaysia, 2009)
Due to a variety of reason, students find it difficult to learn Mathematics. In addition, teachers' efforts to intervene competently in resolving students' difficulties are rendered ineffective by numerous factors. This article reports a survey of 230 primary school regular teachers and 51 Special Educational Needs Assistance (SENA) teachers who attended a Mathematics remediation workshop. Five major and broad categories of findings were obtained from the study. First, participants unanimously endorsed the remediation workshop as useful. Second, they also strongly agreed that the remediation resource package was helpful. Third, the study identified some of the challenges encountered by learners and teachers in remedying Mathematics problems. Fourth, the workshop generated a number of concrete suggestions on how future workshops might be improved. Fifth, Chi-Square analyses revealed statistically significant differences for 10 out of 13 dependent variables. The study recommends repeating the workshop in all four districts in Brunei Darussalam to benefit more teachers and students. Finally, the major implications of the study are also discussed.